(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In today’s digital age, computer literacy has become a fundamental skill for pupils to excel. This study aimed to assess the Computer Literacy Skills among Elementary School Pupils in Argao District 1, Argao, Cebu, Philippines. The study utilized random sampling with 258 respondents selected through Slovin’s formula at 5% margin of error. A questionnaire was used to assess the literacy of the respondents in various basic computer tasks. Data gathered were analyzed using descriptive statistics.